Safety Issues, Security and Risk Management in Nautical Tourism - Kasum, Josip; Žanić Mikuličić, Jelena; Kolić, Vinka (Transactions on Maritime Science, 2018)
The relatively new nautical market gave rise to a special kind of tourism. Nautical tourism as a system has the characteristics of a traffic system with all its peculiarities. Nautical tourism is steadily increasing. In countries nurturing this type of economic activity, nautical tourism has the characteristics of mass tourism. Nautical tourism is a complex system consisting of and using various forms of technical and technological processes. As such it is exposed to various risks. Therefore, this paper proposes a systematic approach to the development of safety measures in nautical tourism.